The Roman Soldier - Watson, G. R. (George Ronald) (New York : Cornell University Press, 1969)
"From the Mediterranean to the British Isles, from the Rhine to the North African desert, the Roman soldier carried his empire's banner to the furthest reaches of the known world. Much has been written about his commanders-men like Caesar, Scipio and Augustus-yet little has been revealed about the life of the individual soldier. The important work gives you a unique look at life in the Legions through the eyes of an ordinary legionary. With lively narrative, the author traces the life of a Roman recruit from induction to retirement. Here, you'll discover fascinating facts on enlistment, basic training, length of service, rewards and punishment, promotion and more. You'll learn how the Roman soldier spent his pay, what he wrote in his letters home and what he did after retirement. This is a classic work-and a must-have reference for students of ancient military history."--Jacket.
Introduction -- The recruit -- The soldier -- Conditions of service -- Religion and marriage -- The soldier in society.
Includes bibliographical references and indexes.
Keywords: Soldiers -- Rome